HUBUNGAN KEPATUHAN PAJAK DAN KEBERLANJUTAN UKM DALAM PERSPEKTIF PLANED BEHAVIOUR THEORY - Alvien , Gunawan; Siti , Mahmudah; Munawaroh , Hapsari (STIE PGRI Dewantara Jombang, 2023)
This research examines the relationship between tax compliance behaviour based on the Theory of Planned Behavior (TPB) and the sustainability of SME businesses. Data collection used a survey method of 107 SMEs with various business fields on the islands of Java and Bali and met the criteria as SME taxpayers based on Government Regulation No. 55 of 2022. This research uses primary data collected through questionnaires given to SME respondents offline and online. Data analysis was carried out using the Spearman rank Correlation Coefficient test to test the research hypothesis. The results of this research show that: 1) understanding of taxation, trust in the government, and intention have a positive relationship with SME taxpayer compliance; 2) there is no significant relationship between obstacles and SME taxpayer compliance; 3) there is a relationship between understanding taxation and trust in the government; 4) trust in the government and obstacles, as well as understanding that taxation and obstacles do not interact with each other; 5) there is a significant relationship between understanding taxation, trust in the government, and tax compliance behaviour of SMEs on the sustainability of SME businesses; and 6) obstacles have no relationship to the sustainability of SME businesses.